TMI Teachers' Preferences for Print and Electronic Media in News Reading Habits in the Digital Era - Zulviatul Ariyanti Majdi; Ahmad Zulfikar Ali (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This thesis is motivated by the adaptation of Islamic boarding school to modernity, which has become an interesting phenomenon to study, as it reflects a paradigm shift in how news and information are accessed. The research questions in this thesis are (1) What are the preferences of female TMI teachers in choosing between print and electronic media for accessing news? (2) What factors influence the preferences of female TMI teachers in selecting news media? (3) What are the implications of these media preferences on the digital literacy of female TMI teachers? This research employs a descriptive qualitative approach. The data sources are female TMI teachers, specifically those serving as community service teachers. Data collection methods used in this study include in-depth interviews, observation, and documentation. Data analysis was carried out through data reduction, data presentation, and concluding. To ensure the validity of the data, source triangulation was used. The findings of this study reveal that the majority of teachers at the female TMI institution prefer electronic media for reading news in the digital era.